꾸지뽕(Cudrania tricuspidata) 열매에서 분리된 조다당의 큰포식세포 면역 활성 조절 - 조은지(Eun-Ji Cho); 김이은(Yi-Eun Kim); 변의홍(Eui-Hong Byun) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2018)
Macrophages play a crucial role in the host immune defense system. The current study investigated immunomodulatory activities induced by polysaccharides extracted from Cudrania tricuspidata (CTPS) fruits in murine macrophages and their role in signaling pathways. In macrophages, CTPS predominantly induced nitric oxide (NO), tumor necrosis factor-a, and interleukin-6 production. In addition, CTPS significantly up-regulated expression of the macrophage surface marker (CD80/ 86 and MHC class I/II). These results indicate that polysaccharides extracted from CTPS may potentially play an immunomodulatory role in macrophages via mitogen-activated protein kinases and nuclear factor-B signaling. These findings may be useful in the development of immune enhancing adjuvant materials obtained from natural sources.